2019
DOI: 10.3390/w11051028
|View full text |Cite
|
Sign up to set email alerts
|

Application of Macrophytes to the Assessment and Classification of Ecological Status above and below the Barrage with Hydroelectric Buildings

Abstract: The key goal of the Water Framework Directive is to achieve a good ecological status in water bodies. The ecological status is mainly determined by the biological elements, which are a very good indicator of the changes taking place in water environments. Thus, this article focuses on the analysis of different methods of assessment of the ecological status of water bodies based on macrophytes used in selected countries in the European Union (the Macrophyte Index for Rivers (MMOR)—Poland; the Mean Trophic Rank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Comprehensive planning and the impact assessment of the activities, including the development of compensatory measures and a monitoring system [61], are necessary. This is in line with the principle of sustainable development, considering natural, social, and economic interests [62].…”
Section: Sloveniasupporting
confidence: 77%
“…Comprehensive planning and the impact assessment of the activities, including the development of compensatory measures and a monitoring system [61], are necessary. This is in line with the principle of sustainable development, considering natural, social, and economic interests [62].…”
Section: Sloveniasupporting
confidence: 77%
“…The analyses carried out with the use of a uniform formula revealed that the detected differences in biomonitoring result not only from the different equations used, but also from the set of species and their ascribed indicator values. The significant differentiation of sets of indicator species considered by various macrophyte systems on lowland rivers has already been demonstrated in the literature [50]. The weaker response of the foreign methods compared with the MIR persisted even when the assessment was based on a uniform equation.…”
Section: Discussionmentioning
confidence: 69%
“…According to Iticescu et al [27], the highest WQI index was in summer 2015 (WQI above 80), and the lowest in winter 2014 (WQI below 50). Tomczyk et al [19] emphasized that, in the assessment of water quality in a river-reservoir system, the physico-chemical properties are important in assessing the degree of water pollution.…”
Section: Water Quality Indexmentioning
confidence: 99%
“…According to Malik and Hashmi [6], surface water is used for various purposes, such as drinking water supply and irrigating farmland; hence, water quality is also closely related to public health. Therefore, monitoring of water quality parameters should be carried out at various points in a river network to prevent river pollution and apply remedial policies [1,19]. The monitoring of water quality is also important in modelling water resources [20] and the distribution of pollutants, source location, and health hazards, in addition to protecting water resources and controlling water pollution [21].…”
Section: Introductionmentioning
confidence: 99%